A retrospective comparison of pregnancy outcomes between women with alpha-thalassaemia 1 trait and normal controls. (17th November 2017) - Traisrisilp, Kuntharee; Jatavan, Phudit; Tongsong, Theera
Abstract: The objective of this retrospective cohort study was to compare pregnancy outcomes between low-risk pregnant women with alpha-thalassaemia-1 trait and normal controls. The database of the Maternal–Foetal Medicine unit was used to identify low-risk singleton pregnant women complicated by alpha-thalassaemia-1 trait who gave birth between January 2002 and October 2014. The low-risk pregnancies with non-carrier status for thalassaemia were assigned into the control group, with a control-to-case ratio of 10:1. During the study period, 595 women with alpha-thalassaemia-1 trait and 5950 normal controls were identified. There was no significant difference in the incidence of preterm birth and most obstetric outcomes between the two groups. However, a statistically significant difference was detected between them in terms of gestational age at delivery, 37.76 ± 2.81 vs. 38.11 ± 2.50 weeks ( p  = .001), birth weight, 2876 ± 581 vs. 2948 ± 527 g ( p  = .002) as well as the rate of low-birth weight, 17.1 vs. 12.8% ( p  = .002). In conclusion, this study provides new insights that alpha-thalassaemia-1 trait has minimal effect on gestational age at delivery and low-birth weight whereas other common adverse pregnancy outcomes are not increased. Impact statement: What is already known on this subject: Thalassaemia trait is associated with some degree of anaemia. What the results of this study add: The prevalence of common adverse outcomes such as preterm birth, stillbirth, low Apgar scores and pregnancy-induced hypertension were not significantly different between both the groups, possibly caused by too small sample size to gain enough power. However, the rate of low-birth weight was significantly increased among pregnancy with alpha-thalassaemia-1 trait. What the implications are of these findings for clinical practice and/or further research: The information may be provided for alpha thalassaemia-1 trait mothers and their families. Physicians should guard against the occurrence of adverse pregnancy in these mothers. Prospective control study should be conducted to overcome the limitation of retrospective nature.